2020
DOI: 10.1177/0954407020950581
|View full text |Cite
|
Sign up to set email alerts
|

Stick–slip oscillations of an engine front-end accessory drive system with a mechanical tensioner

Abstract: This article is aimed to investigate the stick–slip oscillations of an engine front-end accessory drive system with a mechanical tensioner. Based on several assumptions, a generic dynamic model of rotational vibrations of an engine front-end accessory drive system with arbitrary number of accessory pulleys and one mechanical tensioner is established. In this model, the tensioner dry-friction torque is approximated by a hyperbolic tangent function with a scaling factor to control the sticking zone. An improved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…But rotation vibrations of other accessory pulleys do not monotonously decrease with increasing tensioner dry friction. This is consistent with previous conclusions (Zhu et al, 2020b) that give directions of design optimization on tensioner damping.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…But rotation vibrations of other accessory pulleys do not monotonously decrease with increasing tensioner dry friction. This is consistent with previous conclusions (Zhu et al, 2020b) that give directions of design optimization on tensioner damping.…”
Section: Discussionsupporting
confidence: 93%
“…One of the many challenges in successfully developing a good BSG system for a micro-HEV is to maintain its noise and vibrations under different working modes within a comfortable level for passengers and ensure high efficient and reliable start–stop response. Many research studies (Čepon et al, 2009; Kraver et al, 1996; Parker, 2004; Shangguan and Zeng, 2013; Zhu et al, 2018a, 2018b, 2018c, 2020b, 2021) have been conducted on dynamics and vibrations of the traditional EFEADS, but fewer research studies (Canova et al, 2009; Chen, 2009; Feng et al, 2019; Olatunde, 2008) have been conducted on those of the engine accessory drive system with a generator starter (i.e., the BSG system). These research studies are mainly focused on improving performance and efficiency of the starter and generator.…”
Section: Introductionmentioning
confidence: 99%
“…At present, many researchers have established models to describe the hysteresis characteristics of tensioners, which are mainly divided into physical models 2,9 and phenomenological models. [14][15][16][17][18][19][20] Physical model of a tensioner is to characterize the relations of tensioner torque versus angular displacement of tensioner arm with the geometric size of tensioner, the stiffness of tensioner spring and the friction coefficient of friction elements. The physical model is used for structural design and optimization of tensioner to determine the required tensioner torques, and finite element model is a typical physical model.…”
Section: Introductionmentioning
confidence: 99%
“…The parameters in K-V model has clear physical meaning, and it is easy to be used for calculating the dynamic response of tensioner under different excitation, but the calculation accuracy is not high. (2) Dry friction model: Regarding the internal friction of tensioner as coulomb dry friction, Zhu et al 16 and Zhao et al 17 established the dry friction model for tensioner, as shown in Figure 2(b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation